Buzzed : the straight facts about the most used and abused drugs from alcohol to ecstasy - Kuhn, Cynthia; Swartzwelder, Scott; Wilson, Wilkie; Wilson, Leigh Heather; Foster, Jeremy (New York ; London : W.W. Norton & Company, 2014)
Provides current, factual information about many of the most commonly used and abused drugs, looking at how they affect the brain, their short and long term effects, the highs they produce, and the dangers associated with them.
Just say know (a college student's perspective by Leigh Heather Wilson and Jeremy Foster) ; Test your drug knowledge -- pt. I. Alcohol : liquor, whiskey, booze, hooch, wine, beer, ale, porter -- Caffeine : coffee, tea, softdrinks, energy drinks, over-the-counter pain relievers and stimulants, some prescription medications -- Ecstasy : MDMA (X, XTC, Adam), MDE (Eve), MDA (Love) -- Hallucinogens : lysergic acid diethylamide (LSD--acid, blotter, California sunshine, microdot, trip, yellow sunshine, etc.), mescaline (peyote, buttons, mesc, mescal, topi), psilocybin mushrooms (boomers, magic mushrooms, shrooms), dimethyltryptamine (DMT--businessman's special), ayahuasca (caapi, yage, vegetal), belladonna alkaloids (atropine, scopolamine, belladonna, deadly nightshade, Jimsonweed, stink weed, mandrake), phencyclidine (PCP, angel dust, T, PeaCe pill), ketamine (Special K, K), dextromethorphan (Dex, robo, red devils), Salvia divinorum (ska, Maria, la Maria, ska Pastora) -- Herbal drugs : herbal X-tacy, smart drugs, ginseng, melatonin, etc. -- Inhalants : nitrites (butyl or amyl--bolt, bullets, climax, locker room, rush, poppers, snappers, aimes); anesthetics (nitrous oxide--Whippets; gaseous anesthesia agents used for surgery--halothane, ether); solvents, paints, sprays, and fuels (toluene, gasoline, glues, canned spray paint, etc.) -- Marijuana : marijuana (reefer, pot, herb, ganja, grass, old man, Blanche, weed, sinsemilla, bhang, dagga, smoke), hashish (hash, tar), hash oil (oil, charas) -- Nicotine : tobacco, nicotine chewing gum, nicotine skin patch, chewing tobacco, snuff, cigarettes, cigars, pipe tobacco -- Opiates : opium (Chinese molasses, dreams, gong, O, skee, toys, zero), heroin (Big H, dreck, horse, mojo, smack, white lady, brown), heroin and cocain (speedballs), morphine, codeine, hydromorphone (Dilaudid), oxycodone (Percodan, OxyContin), meperidine (Demerol), diphenoxylate (Lomotil), hydrocodone (Vicodin), fentanyl (Sublimaze), propoxyphene (Darvon) -- Sedatives: barbiturates (phenobarbital, pentobarbital [Nembutal], secobarbital [Seconal], amobarbital [Amytal]), chloral hydrate (Notec, Somnos, Felsules), glutethimide (Doriden), Equanil, Miltown, Noludar, Placidyl, Valmid, methaqualone (Quaaludes, ludes), benzodiazepines (such as Rohypnol, Valium, Librium, Ativan, Xanax, Halcion, and many others), drugs designed specifically to induce sleep (zolpidem [Ambien], eszopiclone [Lunesta], and ramelteon [Rozerem]), gamma-hydroxybutyrate (GHB) -- Steroids : steroids, roids, juice -- Stimulants : cocaine (coke, blow, candy, crack, jack, jimmy, rock, nose candy, whitecoat), amphetamine (crank, bennies, uppers), methamphetamine (meth, crystal, crystal meth, ice), ephedrine, methylphenidate (Ritalin), methcathinone (cat, crank, goob) -- pt. II. Brain basics ; Drug basics ; Addiction ; Legal issues.
Includes bibliographical references (pages 355-365) and index.
Keywords: Drugs of abuse -- Popular works